2008
DOI: 10.1097/aln.0b013e31818e3b1b
|View full text |Cite
|
Sign up to set email alerts
|

γ-Aminobutyric Acid–mediated Neurotransmission in the Pontine Reticular Formation Modulates Hypnosis, Immobility, and Breathing during Isoflurane Anesthesia

Abstract: Background Many general anesthetics are thought to produce a loss of wakefulness, in part, by enhancing gamma-aminobutyric acid (GABA) neurotransmission. However, GABAergic neurotransmission in the pontine reticular formation promotes wakefulness. This study tested the hypotheses that: 1) relative to wakefulness, isoflurane decreases GABA levels in the pontine reticular formation; and 2) pontine reticular formation administration of drugs that increase or decrease GABA levels increases or decreases, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 63 publications
(86 reference statements)
8
91
0
1
Order By: Relevance
“…Considered with data showing that delivering hypocretin-1 to the PnO increases GABA levels in the PnO 13 and causes inhibition of some PnO neurons, 10 and with evidence that GABAergic transmission in the PnO is wakefulness promoting, 13,[19][20][21][22][23][24][25] the present results support the interpretation that increasing GABAergic transmission in the PnO is one mechanism by which hypocretin-1 increases wakefulness. The results are discussed below relative to the functional roles of hypocretin-1 in rat PnO and the mechanisms by which hypocretin-1 administered to the PnO causes an increase in wakefulness.…”
Section: Rat 3 Rat 4 Time Post-injection (H)supporting
confidence: 75%
See 2 more Smart Citations
“…Considered with data showing that delivering hypocretin-1 to the PnO increases GABA levels in the PnO 13 and causes inhibition of some PnO neurons, 10 and with evidence that GABAergic transmission in the PnO is wakefulness promoting, 13,[19][20][21][22][23][24][25] the present results support the interpretation that increasing GABAergic transmission in the PnO is one mechanism by which hypocretin-1 increases wakefulness. The results are discussed below relative to the functional roles of hypocretin-1 in rat PnO and the mechanisms by which hypocretin-1 administered to the PnO causes an increase in wakefulness.…”
Section: Rat 3 Rat 4 Time Post-injection (H)supporting
confidence: 75%
“…14 Numerous studies have demonstrated that GABAergic transmission in the PnO increases wakefulness and inhibits REM sleep. 13,[19][20][21][22][23][24][25] The present study provides the first test of the hypothesis that the wakefulness-promoting effects of delivering hypocretin-1 into the PnO are mediated by GABA A receptors as well as by hypocretin receptors. This hypothesis was evaluated by determining whether (1) microinjection of hypocretin-1 into the PnO causes a concentration-dependent increase in wakefulness, (2) this increase in wakefulness is blocked by coadministration of the hypocretin receptor-1 (hcrt-r1) antagonist SB-334867, and (3) coadministration of the GABA A receptor antagonist bicuculline also blocks the wakefulness response to hypocretin-1.…”
Section: The Neuropeptides Hypocretin-1 and Hypo-cretin-2 (Orexin A Amentioning
confidence: 99%
See 1 more Smart Citation
“…Given that GABAergic function in the brain is mediated mainly by GABA A Rs (Lüscher and Keller, 2004), we used bicuculline, an antagonist of GABA A R (Owens and Kriegstein, 2002;Vanini et al, 2008) to investigate this involvement further. Exposure to bicuculline inhibited the swimming activities of 1d.p.f.…”
Section: Role Of Gaba In Larval Swimmingmentioning
confidence: 99%
“…They secrete acetylcholine (Ach) at the nerve ends, both during the physical activity and REM phase. The use of isoflurane and ketamine, as well as other neurotransmitters, is associated with increased amounts of GABA and reduced amounts of Ach in the reticular system [13,14].…”
Section: Sleep Mechanismsmentioning
confidence: 99%